The Problems and Prospects of Culture in Nation Building: The Nigerian Example - Lawal, A. O.; Akerele, E. O.; Akinhanmi, Y.O. Uthman -; Solana, O. L.; Yangomodou, O. D.; Lawal, J. B. (NIU Journal of Social Sciences; Vol 7 No 2 (2021): KIU Journal of Social Sciences, Vol. 7 No. 2, June 2021DO - 10.58709/kiujss.v7i2.1219.27-33, 2021)
Culture is regarded as the way of life of a group of people living in a particular community or society over a specific period of time. Data for this study were collected from secondary sources; through internet materials, journals, textbooks, seminars and commentaries. Results from this study revealed that before venturing on a national or global assignment, it is probably necessary to identify the cultural differences that may exist between one's home country and the country of business operation; where the differences exist, one must decide whether and to what extent the home-country practices may be adapted to the foreign environment. This study therefore recommends and concluded that there is need for entrepreneurs and cultural migrants to learn their client’s culture, promote appreciation of cultural differences, be open to trying new things, exhibit hospitality and be accommodating, everywhere and every time. Keywords: Culture, Nation Building, Nigerians, Problems and Prospects